Ocean Oxygen: the role of the Ocean in the oxygen we breathe and the threat of deoxygenation ... - Marilaure Grégoire; Oschlies, Andreas; Canfield, Donald E.; Castro, Carmen; Ciglenečki, Irena; Croot, Peter; Salin, Karine; Schneider, Birgit; Serret, Pablo; Slomp, Caroline; Tesi, Tommaso; Yucel, Mustafa (Zenodo, 2023)
EMB Future Science Brief No. 10 highlights the most recent science on Ocean oxygen, including causes, impacts and mitigation strategies of Ocean oxygen loss, and discusses whether “every second breath we take comes from the Ocean”. It closes with key policy, management and research recommendations to address Ocean deoxygenation and communicate more accurately about the role of the Ocean in Earth’s oxygen. The sentence “every second breath you take comes from the Ocean” is commonly used in Ocean Literacy and science communication to highlight the importance of Ocean oxygen. However, despite its widespread use, it is often not phrased correctly. In contrast, there is little awareness about the threat of the global oxygen loss in the Ocean, called deoxygenation, particularly in comparison with other important stressors, such as Ocean acidification or increasing seawater temperatures. Deoxygenation is increasing in the coastal and open Ocean, primarily due to human-induced global warming and nutrient run-off ...